Morphological characteristics of young elite paddlers - Alacid, B. F.; Marfell-Jones, M.; Lopez-Minarro, P. A.; Martinez, I.; Muyor, J. M. (Journal of Human Kinetics, 2011)
The aims of this study were to describe kinanthropometric characteristics of elite male and female young paddlers and to compare their proportionality with Olympic paddlers. One hundred and eighty seven young elite sprint paddlers (124 males and 63 females), aged 13 and 14 years, were assessed using a battery of 31 anthropometric dimensions. Somatotypes, Phantom Z-scores and corrected girths were calculated. Comparison between the 13 and 14 year old paddlers showed that 14 year old males had greater height, body weight, sitting height, arm span and upper body lengths, breadths and girths than their 13 year old counterparts, whereas 14 year old female paddlers only differed significantly from the 13 year olds in biacromial breadth and corrected arm girth. Mean somatotypes of male paddlers were best described as balanced mesomorphs, while female paddlers were centrals. Olympic paddlers had higher proportional dimensions in upper body girths, and biacromial breadth in both genders. The data provided in this study could be used as a guideline for talent identification in sprint canoeing and kayaking.